2011
DOI: 10.1016/j.cell.2011.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Isogenic Pluripotent Stem Cells Differing Exclusively at Two Early Onset Parkinson Point Mutations

Abstract: During the course of figure preparation for the above article, we inadvertently redisplayed images from Figure 2G in Figure 5H. The corrected Figure 5 is provided below. Figure 5H demonstrates the ability to generate neuron-specific class III b-tubulin (TUJ1; green) and tyrosine hydroxylase (TH; red) expressing neurons from the genetically corrected Parkinson's disease patient-derived hiPSCs, and the corrected figure does not affect the description of the results in the paper or the conclusions drawn. We regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
228
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(234 citation statements)
references
References 0 publications
5
228
0
1
Order By: Relevance
“…The gene transfer may correct disease-causing point mutations [43] or rescue the phenotype by providing a deficient gene into the safe harbor AAVS1 locus [44]. This approach can be supported by SmartFlare TM Probes in two ways: first, they represent an easy tool to verify the pluripotency status of the iPS cells after the manipulation to identify the most appropriate colonies.…”
Section: Live Screening Of Successfully Reprogrammed Murine Ttfs To Imentioning
confidence: 99%
“…The gene transfer may correct disease-causing point mutations [43] or rescue the phenotype by providing a deficient gene into the safe harbor AAVS1 locus [44]. This approach can be supported by SmartFlare TM Probes in two ways: first, they represent an easy tool to verify the pluripotency status of the iPS cells after the manipulation to identify the most appropriate colonies.…”
Section: Live Screening Of Successfully Reprogrammed Murine Ttfs To Imentioning
confidence: 99%
“…[55,56]). In this study by Soldner and colleagues [54] these mutations have been addressed with genome editing aiming either at correction of a specific mutation (e.g. in PD patient specific hiPSCs) or vice versa at generation of a mutation (e.g.…”
Section: Human Ipscs To Study and Treat Pdmentioning
confidence: 99%
“…A very interesting approach in that respect is a technology known as 'genome editing', employing zinc finger nucleases (ZFNs) to site-specifically target a disease relevant gene. Soldner et al [54] used ZFNs in patientspecific iPSCs to exclusively manipulate a point mutation site in the α-synuclein gene known to be key in rare forms of familial PD [54]. Mutations in α-synuclein at specific sites (e.g.…”
Section: Human Ipscs To Study and Treat Pdmentioning
confidence: 99%
“…They include the progeria syndrome [4,5], Parkinson's disease [6], gyrate atrophy [7] as well as hematological diseases such as Thalassemias [8], Fanconi Anemia [9], and sickle cell anemia [14]. Even though these studies lacked in vivo confirmation of the phenotypic correction, some of them demonstrated functional correction of the phenotype upon differentiation in vitro.…”
mentioning
confidence: 99%
“…Of note, methods based on the application of Helper-dependent Adenoviral Vectors (HDAdVs) have proven successful with editing large genomic regions, potentially allowing for the single-step correction by homologous recombination of genes bearing multiple point mutations or even certain deletions and duplications [5,14]. Most importantly, even though different methods were used in the various reports, gene targeting itself did not seem to affect epi/ genomic integrity [5][6][7]14]. Thus, the broad range of applications for gene editing technologies may not only be circumscribed to gene correction and regenerative medicine, but it could also allow for concise analysis of the molecular mechanisms leading to disease manifestation and progression.…”
mentioning
confidence: 99%